Ventricular arrhythmia and sudden cardiac death in hypertrophic cardiomyopathy: From bench to bedside - Shen, Hua; Dong, Shi-Yong; Ren, Ming-Shi; Wang, Rong (Frontiers in Cardiovascular Medicine, 2022)
Patients with hypertrophic cardiomyopathy (HCM) mostly experience minimal symptoms throughout their lifetime, and some individuals have an increased risk of ventricular arrhythmias and sudden cardiac death (SCD). How to identify patients with a higher risk of ventricular arrythmias and SCD is the priority in HCM research. The American College of Cardiology/American Heart Association (ACC/AHA) and the European Society of Cardiology (ESC) both recommend the use of risk algorithms to identify patients at high risk of ventricular arrhythmias, to be selected for implantation of implantable cardioverters/defibrillators (ICDs) for primary prevention of SCD, although major discrepancies exist. The present SCD risk scoring systems cannot accurately identify early-stage HCM patients with modest structural remodeling and mild disease manifestations. Unfortunately, SCD events could occur in young asymptomatic HCM patients and even as initial symptoms, prompting the determination of new risk factors for SCD. This review summarizes the studies based on patients' surgical specimens, transgenic animals, and patient-derived induced pluripotent stem cells (hiPSCs) to explore the possible molecular mechanism of ventricular arrhythmia and SCD. Ion channel remodeling, Ca2+ homeostasis abnormalities, and increased myofilament Ca2+ sensitivity may contribute to changes in action potential duration (APD), reentry circuit formation, and trigger activities, such as early aferdepolarization (EAD) or delayed afterdepolarization (DAD), leading to ventricular arrhythmia in HCM. Besides the ICD implantation, novel drugs represented by the late sodium current channel inhibitor and myosin inhibitor also shed light on the prevention of HCM-related arrhythmias. The ideal prevention strategy of SCD in early-stage HCM patients needs to be combined with gene screening, hiPSC-CM testing, machine learning, and advanced ECG studies, thus achieving individualized SCD prevention.